Pengaruh Struktur Modal Berdasarkan Profitabilitas, Pertumbuhan Aset, dan Ukuran Perusahaan pada Perusahaan Manufaktur - Dwijayanti, Nita; Hady, Hamdy; Elfiswandi (SAFE-Network, 2019)
This study aims to measure the level of influence of profitability, asset growth, and company size on changes in capital structure in manufacturing companies. The method used for sample determination is purposive sampling with analytical methods using descriptive statistics, classic assumption tests and multiple panel data regression. The data tested in the study were 112 companies in the basic and chemical industry sectors, consumer goods, and the textile and garment sub-sector listed on the Indonesia Stock Exchange (IDX). The results showed that partially profitability had a negative and significant effect on capital structure, while asset growth had a positive and significant effect. Then the company must be able to choose the right combination of financing sources in order to be able to produce optimal profits.